Fish Oil Supplementation Reduces Heart Levels of Interleukin-6 in Rats with Chronic Inflammation due to Epilepsy - Nejm, Mariana Bocca; Haidar, André Abou; Hirata, Aparecida Emiko; Oyama, Lila Missae; de Almeida, Antonio-Carlos Guimarães; Cysneiros, Roberta Monterazzo; Cavalheiro, Esper Abrão; Scorza, Carla Alessandra; Scorza, Fulvio Alexandre (Frontiers in Neurology, 2017)
Sudden unexpected death in epilepsy (SUDEP) is the major cause of premature death related to epilepsy. The causes of SUDEP remain unknown but cardiac arrhythmias have been suggested as a major mechanism of its fatal event. Inflammation has been implicated in the pathogenesis of both epilepsy and ventricular arrhythmia, with interleukin-6 (IL-6) being recognized as a crucial orchestrator of the inflammatory states. Our group previously reported that levels of IL-6 were increased in the heart of epileptic rats. In this scenario, anti-inflammatory actions are among the beneficial effects of fish oil dietary. This investigation revealed that elevated heart levels of IL-6 were marked reduced in epileptic rats long-term treated with fish oil, suggesting protective anti-inflammatory actions against the dangerous high levels of IL-6. Based on these findings, our results suggest the beneficial effects of long-term intake of fish oil on reducing the inflammation associated with chronic epilepsy.